2017
DOI: 10.1371/journal.pone.0187342
|View full text |Cite
|
Sign up to set email alerts
|

Motor-based bodily self is selectively impaired in eating disorders

Abstract: BackgroundBody representation disturbances in body schema (i.e. unconscious sensorimotor body representations for action) have been frequently reported in eating disorders. Recently, it has been proposed that body schema relies on adequate functioning of the motor system, which is strongly implicated in discriminating between one’s own and someone else’s body. The present study aimed to investigate the motor-based bodily self in eating disorders and controls, in order to examine the role of the motor system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
0
14
1
Order By: Relevance
“…This finding contrasts with recent study by Campione et al (2017), which compared women with disordered eating and age-and gender-matched controls in their ability to implicitly recognise their own body. The results showed that women with EDs differed from controls in their ability to process self-stimuli vs. non-self-stimuli and did not demonstrate the classic self-body advantage.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding contrasts with recent study by Campione et al (2017), which compared women with disordered eating and age-and gender-matched controls in their ability to implicitly recognise their own body. The results showed that women with EDs differed from controls in their ability to process self-stimuli vs. non-self-stimuli and did not demonstrate the classic self-body advantage.…”
Section: Discussioncontrasting
confidence: 99%
“…In the future, these visual hand recognition tasks must be investigated in persons suffering from eating disorders. In fact, Campione et al (2017) have already applied these visual hand tasks to eating disorder outpatient, but they did not report the results of the relationship between task performance and body image in the self-other discrimination task.…”
Section: Discussionmentioning
confidence: 99%
“…All participants performed the laterality judgment task first, followed by the self-other discrimination task on the same day (cf. Campione et al, 2017 ). We adopted this order to minimize participants’ attention to hand ownership when completing the laterality judgment task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the LRJT for the hand and the foot can be implemented to evaluate the body schema because it uses an implicit motor imagery, whereas the LRJT which contains multiple body parts should be implemented with caution. Eating disorder [56] Asperger syndrome [57] Locked in syndrome [58,59] Developmental coordination disorder [60] Asomotognosia [61] Spinal cord injury [62] Asall Kim, Chung-hwi Yi…”
Section: Discussionmentioning
confidence: 99%